Mucopolysaccharide from cuttlefish: Purification, chemical characterization and bioactive potential. (1st July 2017) - Seedevi, Palaniappan; Moovendhan, Meivelu; Vairamani, Shanmugam; Shanmugam, Annaian
Highlights: The Uronic acid was contributed more it as 50.11%. The Sulfate was found higher it as 27.69%. The molecular weight of GAG was calculated as 17 kDa. The sulfated GAG has showed promising anticoagulant and anticancer activities. Abstract: The sulfated mucopolysaccharide (GAG) was isolated from S. pharonis and the carbohydrate and protein content was found to be 62.4% and 3.9%. The disaccharide profile of sulfated GAG composed glucuronic acid, N-acetyl glucosamine and sulfate content by contributing 50.11%, 38.00% and 27.69% respectively. The carbon, hydrogen and nitrogen content of the sulfated GAG showed 14.80%, 1.68% and 2.99% respectively. The molecular weight of sulfated GAG was calculated as 27 kDa and the structural characterization was done by Fourier Transform Infrared (FT-IR) and NMR Spectroscopy. The Activated Partial Thromboplastin Time (APTT) and Prothrombin Time (PT) of sulfated GAG were determined as 91 IU and 39.55 IU at 25 μg/ml respectively. Further the sulfated GAG reported the cytotoxic effect (CC50 ) of 1100 μg/ml concentration on Vero cell line. The sulfated GAG reported the anticancer activity against HeLa cell line with an inhibition rate of 18.65%–66.13% at 50–250 μg/ml concentration. The sulfated GAG can be considered as a potent anticoagulant and anticancer drug in future.